GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 9941 species occurrences available in GBIF matching the query: TaxonKey: Aspidoscelis Fitzinger, 1843. The dataset includes 9941 records from 32 constituent datasets: 117 records from NatureServe Network Species Occurrence Data. 1 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 2049 records from KUBI Herpetology Collection. 50 records from LACM Vertebrate Collection. 4 records from CHAS Herpetology. 3 records from Angelo State Natural History Collections (ASNHC) - Herpetology Collection. 10 records from Geographically tagged INSDC sequences. 29 records from TNHC Herpetology Collection. 3 records from Macaulay Library Audio and Video Collection. 1396 records from UCM Amphibian and Reptile Collection (Arctos). 8 records from New Mexico Biodiversity Collections Consortium database. 52 records from NMNH occurrence DwC-A. 24 records from Herpetology Collection. 44 records from Tissues Specimens. 94 records from Museum of Comparative Zoology, Harvard University. 1 records from herpetology. 1172 records from CAS Herpetology (HERP). 297 records from MVZ Herp Collection (Arctos). 588 records from AMNH Herpetology Collections. 2531 records from Arizona State University Amphibian and Reptile Collection. 1 records from Collection Herpetology SMF. 3 records from Queensland Museum provider for OZCAM. 287 records from SDNHM Herpetology Collection. 82 records from UTA Herpetology. 3 records from FHSM Herps Collection. 59 records from Coleccion de Herpetologia, MZFC-UNAM. 45 records from Colección Herpetológica del Museo de Zoología "Alfonso L. Herrera", México (MZFC, UNAM). 31 records from iNaturalist research-grade observations. 831 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 9 records from UWBM Herpetology Collection (Arctos). 67 records from Reptile Specimens. 50 records from UTEP Vertebrates.
Keywords: GBIF; biodiversity; species occurrences